2023
DOI: 10.1080/22221751.2022.2161422
|View full text |Cite
|
Sign up to set email alerts
|

Cross-neutralization and viral fitness of SARS-CoV-2 Omicron sublineages

Abstract: The rapid evolution of SARS-CoV-2 Omicron sublineages mandates a better understanding of viral replication and cross-neutralization among these sublineages. Here we used K18-hACE2 mice and primary human airway cultures to examine the viral fitness and antigenic relationship among Omicron sublineages. In both K18-hACE2 mice and human airway cultures, Omicron sublineages exhibited a replication order of BA.5 ≥ BA.2 ≥ BA.2.12.1 > BA.1; no difference in body weight loss was observed among different sublineage-infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Another limitation of our research may be the fact that the Enzyme-Linked Immunosorbent Assay (ELISA) assay was coated with a particular Omicron subvariant (BA.1) limiting the generalizability of our finding to other Omicron subvariants. However, antigenic mapping studies revealed Omicron subvariants to be antigenically distinct to previous VOCs (44)(45)(46), and individuals responding to the BA.1 subvariant have been shown to exhibit more comparable humoral immune response among other Omicron subvariants as opposed to more antigenically distinct pre-Omicron variants and vice versa (44,47). This relation between Omicron subvariants is also reflected in clinical data, showing a similar disease severity among Omicron subvariants (26).…”
Section: Strengths and Limitationsmentioning
confidence: 84%
“…Another limitation of our research may be the fact that the Enzyme-Linked Immunosorbent Assay (ELISA) assay was coated with a particular Omicron subvariant (BA.1) limiting the generalizability of our finding to other Omicron subvariants. However, antigenic mapping studies revealed Omicron subvariants to be antigenically distinct to previous VOCs (44)(45)(46), and individuals responding to the BA.1 subvariant have been shown to exhibit more comparable humoral immune response among other Omicron subvariants as opposed to more antigenically distinct pre-Omicron variants and vice versa (44,47). This relation between Omicron subvariants is also reflected in clinical data, showing a similar disease severity among Omicron subvariants (26).…”
Section: Strengths and Limitationsmentioning
confidence: 84%
“…Infectious virus from experiments was quantified using plaque assays performed as previously described using Vero E6-TMPRSS2 cells [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…HAE cells were infected with a mix of the WA1 or mutant virus with an equal MOI of 0.4 and samples were collected as previously described [ 30 ]. For analysis, RNA was purified from each sample and cDNA fragments corresponding to codon positions 72–147 of nsp6 were generated using the SuperScript™ IV One-Step RT–PCR System.…”
Section: Methodsmentioning
confidence: 99%
“…All cells were maintained at 37°C with 5% CO2. The infectious clones derived USA-WA1/2020 SARS-CoV-2, ∆3678, and the BA.5 variant were generated as previously described [7,17,18].…”
Section: Methodsmentioning
confidence: 99%